2022
DOI: 10.1021/acs.jcim.2c00057
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanics/Molecular Mechanics Studies on the Catalytic Mechanism of a Novel Esterase (FmtA) of Staphylococcus aureus

Abstract: FmtA is a novel esterase that shares the penicillinbinding protein (PBP) core structural folding but found to hydrolyze the removal of D-Ala from teichoic acids. Molecular docking, dynamics, and MM-GBSA of FmtA and its variants S127A, K130A, Y211A, D213A, and K130AY211A, in the presence or absence of wall teichoic acid (WTA), suggest that active site residues S127, K130, Y211, D213, N343, and G344 play a role in substrate binding. Quantum mechanics (QM)/molecular mechanics (MM) calculations reveal that during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…1.XX of the Avogadro molecular builder tool [ 43 ], and was subsequently converted to PDB format using the PyMOL Molecular Graphics System. The ligand (RXn-02) and receptors (target proteins) were prepared for the addition of hydrogen atoms (polar only), removal of water (H 2 0) molecules, and the addition of Kollman charges [ [44] , [45] , [46] ], prior to the docking simulation according to the methods described in previous studies [ 47 , 48 ]. Docking simulations were conducted using the default settings of AutoDock Vina (vers.…”
Section: Introductionmentioning
confidence: 99%
“…1.XX of the Avogadro molecular builder tool [ 43 ], and was subsequently converted to PDB format using the PyMOL Molecular Graphics System. The ligand (RXn-02) and receptors (target proteins) were prepared for the addition of hydrogen atoms (polar only), removal of water (H 2 0) molecules, and the addition of Kollman charges [ [44] , [45] , [46] ], prior to the docking simulation according to the methods described in previous studies [ 47 , 48 ]. Docking simulations were conducted using the default settings of AutoDock Vina (vers.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved residues of the catalytic triad have different roles: Ser functions as a nucleophile, Lys works in acylation/deacylation, while Tyr holds the substrate in the course of hydrolysis of WTA . The QM/MM study suggested that the release of d -Alanine from WTA involves the formation of an acyl–enzyme complex and two tetrahedral intermediate complexes, which are stabilized via oxyanion hole residues (backbone amide of Ser127 and Gly344) . Therefore, in FmtA, the first motif residues (Ser127 and Lys130) were involved in catalysis and charge neutralization; second motif (Tyr211 and Asp213) in holding the substrate; and third motif (Asn343 and Gly344) is crucial for the stability and charge neutralization of WTA …”
Section: Discussionmentioning
confidence: 99%
“…DFT calculation was done to evaluate the polarity of drugs (gemifloxacin, paromomycin, streptomycin, and tobramycin) . The molecular electrostatic potential and molecular orbital energies were assessed by using B3LYP with the basis set of 6-311G (d,p), as done by Dalal et al ,,,, Furthermore, quantum mechanics/molecular mechanics (QM/MM) estimations for FmtA–drug(s) complexes were conducted using our own N-layered integrated molecular orbital and molecular mechanics (ONIOM) method, as done by Dalal et al ,,, The inhibitor and side chain atoms of Ser127, Lys130, Tyr211, and Asp213 were considered in the QM layer, whereas the remaining part of the protein was put in the MM layer. The enthalpy (Δ H ), relative Gibbs free energy (Δ G ), and entropy (Δ S ) were assessed by ONIOM (B3LYP/6-311G­(d,p): AMBER).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations